Rise in intraluminal temperature during ureteroscopy: Is this a concern? - Hyung Joon Kim; Sung Kyu Hong (Investigative and Clinical Urology)
The global increase in urolithiasis prevalence has led to a shift towards minimally invasive procedures, such as retrograde intrarenal surgery, supported by advancements in laser technologies for lithotripsy. Pulsed lasers, particularly the holmium YAG and the newer thulium fiber laser, have significantly transformed the management of upper urinary tract stones. However, the use of high-power lasers in these procedures introduces risks of heat-related injury. Laser lithotripsy works through photothermal and photomechanical effects to fragment stones, but up to 96% of the laser energy is converted into heat, increasing the risk of thermal damage to the surrounding urothelial mucosa. Studies show that even at low-power settings, intrarenal temperatures can exceed the threshold for cellular injury, particularly in confined spaces like the ureter. This narrative review explores strategies to mitigate thermal injury, including optimizing laser settings, improving irrigation flow rates, and incorporating novel methods such as cold irrigation, controlling outflow resistance, and using suction. Understanding these approaches is crucial to enhancing patient safety during high-power laser lithotripsy procedures.